Examining health sciences students' intention to uptake COVID-19 vaccination using the theory of planned behavior - Salah S. Alshagrawi (Taylor & Francis Group, 2023)
To examine the association between the theory of planned behavior (TPB) constructs and Health Sciences students' intentions to receive COVID-19 vaccination. A cross-sectional study was conducted in Saudi Arabia by recruiting Health Sciences students as participants. Using Structural Equation Modeling (SEM), the proposed TPB model was evaluated. The sample of 505 individuals consisted of more males (n = 275; 54.5%) than females and was relatively young (88% were between the ages of 18 and 30). The suggested TPB model explained 78.2% of the variation in intention to get COVID-19 immunization. We found that greater levels of perceived behavioral control (β = 1.58, p < .001) and attitude (β = .44, p < .001) strongly predicted increased vaccination intentions. The subjective norm construct was not a significant predictor of vaccination intentions (β = 0.06, p = .34). The findings of this study indicate that the TPB can be utilized effectively to obtain insight into the factors associated with COVID-19 adherence and help in the development of effective COVID-19 intervention strategies.